PELATIHAN PEMBUATAN AKUN MARKETPLACE BAGI PELAKU UMKM DALAM MENDUKUNG PENINGKATAN PEREKONOMIAN DESA DI KABUPATEN INDRAMAYU - Taupiqqurrahman, Taupiqqurrahman; Dirkareshza, Rianda; Ramadhani, Dwi Aryanti; Hindira DPS, Ratna (Abdi Masyarakat, 2022)
Jatisura Village is one of the villages in Indramayu Regency, West Java Province. The village has advantages that other villages do not have. In Jatisura Village, there is a UMKM Rolisa Food, this UMKM has six products in packaged form.  The six products include Mango Crackers, Mango Bean Coffee, Candied Mangoes, Mango Juice, Orange Leaf Beans and Cowhide Krupuk. However, the problem is that the UMKM of Rolisa Food has not been able to sell the UMKM products and only sell conventionally. Meanwhile, at this time the development of increasingly advanced technology has an impact on digital-based sales and advertising. The activity was carried out in the form of Training on Making Maketplace Accounts for the UMKM Actors in Supporting the Improvement of the Village Economy in Indramayu Regency. The pre-test results are at 27.7% and after the activity is completed through a posttest by filling out a questionnaire using google form media with post test results with results at approximately 83.3%, there is a difference of approximately 55.6%, which explains that there is an increase in knowledge after being given by the service team.